Electrical Conductivity (Resistivity) Measurement of ω Titanium - Masuda, Takahiro; Kitahara, Hiromoto; Mito, Masaki; Nishiyama, Norimasa; Horita, Zenji; Fukunaga, Kosuke; Naragino, Kaishi (MATERIALS TRANSACTIONS, 2025)
This study presents measurements of electrical conductivity and Vickers microhardness of ω phase in pure Ti. Samples containing 100% ω phase is produced by a high-pressure synthesis under an elevated temperature. The results are compared with those of 100% α phase in an as-received state and of the samples processed by high-pressure torsion (HPT) where severe plastic strain is imposed under a high pressure. For the electrical conductivity measurement, a contactless method using a superconducting quantum interference device magnetometer is employed, which allows the measurement over a wide range of temperature down to the liquid helium temperature. Vickers microhardness measurement is conducted for the ω phase under different applied loads to minimize the effect of reverse transformation from the ω phase to the α phase during the measurement. Microstructures are observed by electron back scatter diffraction analysis, showing that the grain size is of ∼12 µm containing less dislocations, and this structure is in contrast with the HPT-processed sample having high densities of dislocations and grain boundaries. This difference in the microstructure results in appreciably lower electrical conductivity in a temperature range below ∼100 K for the HPT-processed sample. No anomaly of a superconductive signal is detected in the ω phase down to the temperature of 1.8 K, suggesting that a superconductive state does not exist at ambient pressure in the corresponding temperature range.